Journeys to the Other Shore : Muslim and Western Travelers in Search of Knowledge - Euben, Roxanne Leslie, 1966- (Book collections on Project MUSE., 2008)
The contemporary world is increasingly defined by dizzying flows of people and ideas. But while Western travel is associated with a pioneering spirit of discovery, the dominant image of Muslim mobility is the jihadi who travels not to learn but to destroy. Journeys to the Other Shore challenges these stereotypes by charting the common ways in which Muslim and Western travelers negotiate the dislocation of travel to unfamiliar and strange worlds. In Roxanne Euben's groundbreaking excursion across cultures, geography, history, genre, and genders, travel signifies not only a physical movement acr.